(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The search deals approach of Syrian legislator abuse of drugs or addiction on it. That through three chapters: The first chapter regards with types or forms of criminal activity as determined the article 43 of drugs law which are possession, detention, buying, transportation, surrender, submission. And this chapter studies nature of drugs, and analyse judicial opinions with regard problem seizing of drugs. The second chapter treats intention of drugs taking, and necessity of knowing nature of narcotic substance from side taker it, and ways of deduction this knowing, and necessity of recording this knowing within the judgment, and lastly addressing willing of taking the narcotic substance, and ways of proving willing of taking the narcotic substance. The third chapter studies, the penalties for crime of abuse of drugs, and measure of placement in medical centre.